Modification of Milk Fat: Modification of Milk Fat - Nadeem, Muhammad (Biological Sciences - PJSIR, 2015)
The potential health benefits associated with the intake of unsaturated fatty acids for the reduction of bad LDL cholesterol has been scientifically proven. Concentration of unsaturated fatty acids in milk and dairy products can be increased by many ways, however, many of the modification strategies do not have any significant impact on the reduction of cholesterol from milk and milk prodcuts. The concentration of unsaturated fatty acids in milk fat can also be decreased by dry fraction, interesterification, transeterification etc. Milk products with higher magnitude of unsaturated fatty acids may have significant influence on the reduction of serum cholesterol.